An Uncommon Presentation of Adrenal Cyst with Subclinical Cushing's Syndrome: A Diagnosis Dilemma. (1st September 2021) - Tahri, A.; Abdellaoui, W.; Benyakhlef, S.; Boujtat, K.; Mahroug, I.; Kamaoui, I.; Barki, A.; Kettani, F.; Rouf, S.; Latrech, H.
Abstract : Adrenal cysts are a rare entity that is usually nonfunctional and asymptomatic. Their association with adrenal neoplasms was rarely described in the literature. We report a unique case of a 40 -year-old woman who was referred for evaluation of a left adrenal incidentaloma with subclinical Cushing's syndrome. The tumor was suspicious for malignancy regarding computed tomography scan (CT scan) features. Therefore, a laparoscopic left partial adrenalectomy was performed. Pathology examination showed multilocular spaces lined by endothelial cells which are compatible with endothelial adrenal cyst, associated to an adrenocortical adenoma. We further discuss the management of adrenal cyst with review of the literature.